QUESTIONS OF STAR-SHAPED LINES IN PUBLIC PASSENGER MASS TRANSPORT (Perner's Contacts, 2011)
The paper is focused on design of star-shaped lines in public passenger mass transport. The main contribution of application of these lines in integrated public passenger transport systems is seen in field of designing of supplementary lines to generic lines. Technological aspects of design and rationalizing of these lines are mentioned in the paper. Relation to transport demand models is also mentioned. Illustrational case of design of line in relation to transport demand is mentioned on the end of the paper.
Keywords: integrated transport system; transport demand; line; public passenger mass transport